2013
DOI: 10.4172/2155-9546.1000159
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Serum Calcium and 17β-Estradiol Levels in Persian Sturgeon, Acipenser persicus

Abstract: Concentrations of total serum calcium and17β-estradiol (E2) were measured during four stages of ovarian growth in Persian sturgeon, Acipenser persicus. Total calcium and E2 increased from stage II (cortical alveolus) and reached their highest levels (6.67 ± 1.15 mg/dl and 5.33 ± 1.06 ng/ml, respectively) during stage III (vitellogenic). Levels of both total calcium and E2 decrease during stage IV (ripe). A decline in serum calcium level was observed postspawning (stage V). Total serum calcium exhibited a linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…These lower values are explained by the smaller lengths and weights of the organisms sampled in their study, compared to the ones in our study; but, since a limited period of time was monitored here, the verification of the inverse relationship between GSI and K could not be performed for this work. The E2 analysis could be performed only in plasma samples of ripe and spent females, and their mean values of 6.68 and 3.84 ng ml -1 , respectively, are comparable, though slightly higher, to values reported for three different stages of ovarian development of wild female Persian sturgeon, Acipenser persicus, they were the vitellogenic stage III (E2: 5.33 ng ml -1 ), the ripe stage IV (E2: 1.98 ng ml -1 ) and the ovulation stage V (E2: 2.31 ng ml -1 ; Hosseinzadeh et al, 2013), while Semenkova et al (2002) reported that E2 concentration in plasma of stellate sturgeon (Acipenser stellatus) ranged from 1.22 to 2.05 ng ml -1 and decreased to 0.16 ng ml -1 after ovulation, a similar trend for the E2 values observed in this study.…”
Section: Discussionsupporting
confidence: 77%
“…These lower values are explained by the smaller lengths and weights of the organisms sampled in their study, compared to the ones in our study; but, since a limited period of time was monitored here, the verification of the inverse relationship between GSI and K could not be performed for this work. The E2 analysis could be performed only in plasma samples of ripe and spent females, and their mean values of 6.68 and 3.84 ng ml -1 , respectively, are comparable, though slightly higher, to values reported for three different stages of ovarian development of wild female Persian sturgeon, Acipenser persicus, they were the vitellogenic stage III (E2: 5.33 ng ml -1 ), the ripe stage IV (E2: 1.98 ng ml -1 ) and the ovulation stage V (E2: 2.31 ng ml -1 ; Hosseinzadeh et al, 2013), while Semenkova et al (2002) reported that E2 concentration in plasma of stellate sturgeon (Acipenser stellatus) ranged from 1.22 to 2.05 ng ml -1 and decreased to 0.16 ng ml -1 after ovulation, a similar trend for the E2 values observed in this study.…”
Section: Discussionsupporting
confidence: 77%
“…In other hand, female vitellogenin (VTG) starts to produce in response to increasing estradiol levels during development of oocytes, while in male is low or lacks VTG. These data are supported from earlier reports in other sturgeon species, where plasma or serum17β-estradiol level increased from the pre-vitellogenic to the vitellogenesis stage and reached its highest level in the post-vitellogenic stage (WEBB et al, 2002;WILDHABBER et al, 2007;HOSSEINZADEH et al, 2013;Carolyn et al, 2016;YOUNESZADEH-FASHALAMI et al, 2018). Actually, the lack of huge differences in E2 values between the both sex was expected, as immature individuals are known to have the lowest basal levels (WHEELER et al, 2016), in contrast to female Siberian sturgeon in stage IV, which correspond to the maximum incorporation of vitellogenin (PELISSERO et al, 1989).…”
Section: Resultssupporting
confidence: 86%
“…Over the May-October period, values ranging from approximately 0.8 to 5.0% for females and from 0.1 to 2.5% for males have been reported for Sciaena umbra [35]. On the other hand, the concentration of plasma E 2 , which has been shown to decrease as gonad maturity progresses in fish, is considered as another indicator of gonad development [39]. In the present study, levels found in wild females and males were 0.007 and 0.006 ng mL -1 , respectively.…”
Section: Discussionmentioning
confidence: 99%